Mass photography : collective histories of everyday life - Pollen, Annebella (International library of visual culture, 2016)
With increasingly accessible camera technology available, crowdsourced collective histories of everyday life, harnessing amateur photographers to secure a snapshot of a single day, abound like never before. 'Mass photography' assesses the potential of these popular moment-intime projects by examining their historical predecessors. For the first time, it views the vast photographic collections resulting from such projects, analysing their structures and systems, their aims and objectives, and their claims and promises. The central case study is of 55,000 photographs submitted to One Day for Life in 1987, which aimed, in its own time, to be 'the biggest photographic event the world had ever seen'. 'Mass photography' also makes a new and valuable contribution by taking a fresh look at amateur photographic practice on an unprecedented scale.